A degree-based account of wh-exclamatives in Catalan - Castroviejo Mir´o, Elena (Proceedings of Sinn und Bedeutung, 2019)
In this paper I show that exclamatives in Catalan should be analyzed as a special type of degree construction. It is special because its contribution to discourse is not that of a declarative clause, but rather that of a degree construction – similar to a comparative clause or a result clause construction – because it includes a degree modifier that establishes an equative relation between two degrees. Additionally, I discuss the previous literature on exclamatives and argue that their proposals, according to which exclamatives should be approached from the semantics of questions, are not satisfactory enough to account for the data from Catalan.